2022
DOI: 10.1029/2021jc018356
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Magnitude of Subsurface Anomalies During the Northeast Pacific Blob as Measured by Animal‐Borne Sensors

Abstract: Marine heatwaves (MHWs) are prolonged warm water events that are increasing in frequency and magnitude due to rising global temperatures. The Northeast Pacific Blob was an unusually widespread MHW that affected ecosystems across the Northeast Pacific, from producers to top predators. Temperature and salinity data collected by northern elephant seals (Mirounga angustirostris) from 2014 to 2017 show significant (>2 sd) warm anomalies throughout the top 1,000 m of the water column, with peak warming in late 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 102 publications
2
15
0
Order By: Relevance
“…The Blob lasted through 2016 in the upper 0-100-m layer yet lingered through 2017-2018 in the subsurface 100-200-m layer as documented by Freeland and Ross (2019), who also noted a possible return in late 2018 of a warm anomaly (Figure 3), which actually occurred in 2019 as reported by Scannell et al (2020). During the first years, The Blob's manifestation in the surface layer diminished, while its manifestation in the subsurface markedly increased as noted by Freeland and Ross (2019), Zhi et al (2019), and Holser et al (2022), among others (Figure 3). The Blob's impact on the marine ecology of the Northeast Pacific was dramatic in terms of magnitude, duration, and spatial extent.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The Blob lasted through 2016 in the upper 0-100-m layer yet lingered through 2017-2018 in the subsurface 100-200-m layer as documented by Freeland and Ross (2019), who also noted a possible return in late 2018 of a warm anomaly (Figure 3), which actually occurred in 2019 as reported by Scannell et al (2020). During the first years, The Blob's manifestation in the surface layer diminished, while its manifestation in the subsurface markedly increased as noted by Freeland and Ross (2019), Zhi et al (2019), and Holser et al (2022), among others (Figure 3). The Blob's impact on the marine ecology of the Northeast Pacific was dramatic in terms of magnitude, duration, and spatial extent.…”
Section: Introductionmentioning
confidence: 58%
“…The stratification barrier notwithstanding, The Blob gradually extended to the subsurface over 2014-2016 as documented by Freeland and Ross (2019). Temperature and salinity data collected in 2014-2017 by instrumented northern elephant seals in the NE Pacific were analyzed by Holser et al (2022) to provide evidence of The Blob extending eventually to 1000 m depth. The vertical extent of The Blob is essential with regard to its propagation to the Bering Sea via the Aleutian Straits where the shallow depths of some passes will constrain water transport as discussed below; for more information see the latest geomorphological study of the Aleutian passes by Zimmerman and Prescott (2021).…”
Section: Formation Evolution and Propagation Of The Blob To The Berin...mentioning
confidence: 99%
“…Scannell et al. (2020) demonstrated that the heat anomalies from this event were lingering for years at depth, affecting ecosystems for much longer periods than diagnosed from the surface only (see also Freeland & Ross, 2019; Holser et al., 2022; Jackson et al., 2018). Due to the wide spacing (scriptO $\mathcal{O}$ of 100 km) of the Argo float profiles and their 10 days repeat cycle, these authors had to average the data considerably in time and space, thereby losing much detail.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Johnson et al (2022) and Scannell et al (2020) used Argo float data to investigate the vertical extent and propagation of the Northeast Pacific Blob heatwave, that is, the strong surface MHW in the Northeastern Pacific that lasted for multiple years ( , Bond et al, 2015Di Lorenzo & Mantua, 2016) and was likely even a compound extreme (Gruber et al, 2021). Scannell et al (2020) demonstrated that the heat anomalies from this event were lingering for years at depth, affecting ecosystems for much longer periods than diagnosed from the surface only (see also Freeland & Ross, 2019;Holser et al, 2022;Jackson et al, 2018). Due to the wide spacing ( 𝐴𝐴  of 100 km) of the Argo float profiles and their 10 days repeat cycle, these authors had to average the data considerably in time and space, thereby losing much detail.…”
mentioning
confidence: 99%
“…Nevertheless, a few noteworthy studies (e.g., Hu et al., 2021; Schaeffer & Roughan, 2017) have been able to identify MHWs in the subsurface using observations from buoys with daily temperature data (though such records are rare) and with hindcast models (Amaya et al., 2023a; Chen et al., 2015; Großelindemann et al., 2022; Oliver et al., 2018; Ryan et al., 2021). Additionally, less frequently sampled data sets (i.e., Argo floats, animal mounted sensors, and CTD casts), have been used to examine the subsurface temperature anomalies during identified surface events, allowing for an initial look at the subsurface temperature structure associated with MHWs (Elzahaby & Schaeffer, 2019; Freeland & Ross, 2019; Holser et al., 2022; Jackson et al., 2018; Scannell et al., 2020). These studies have shown that MHWs in the global oceans have the potential to last longer and at a greater intensity (e.g., positive temperature anomalies) than what is indicated by their surface signature, thereby increasing the potential impact on marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%